Nana Gutiérrez - Poetic Butterfly: An Unjustly Marginalized Subversive Writer - Rojas Pachas, Daniel (2024)
This article seeks to contribute to a fair representation of Nana Gutiérrez as an author. The main objective of this article is to provide an update of her texts through a reading that pays attention to the textual procedures of antipoetry and dialogism with the corresponding use of taxonomies, vocatives, and forms of colloquial language along with the appropriation of communication resources of the mass media. This article also prioritizes the study of the symbolism that Nana gives to the butterfly as a representative element of her voice in poetry.